Аналіз поновлюваного альтернативного джерела отримання електричної енергії - Білоус, М. Ю.; Медова, К. Г. (ХНУРЕ, 2020)
The paper analyzes the renewable alternative source of electricity – solar energy. Possible options for improving efficiency are considered. The main advantages and disadvantages of using solar energy are analyzed.
Keywords: сонячна енергетика; сонячні панелі